BIOACUMULAÇÃO DE METAIS E PRESENÇA DE METALOTIONEÍNA NO CARANGUEJO-UÇÁ, Ucides cordatus (LINNAEUS, 1763). - ROCHA, Carmen Hellen da Silva (2017)
The urbanization and industrialization processes in coastal regions generate residues that can impact local biota, being heavy metals the elements of great relevance in estuaries. These contaminants can be assimilated by organisms that can accumulate in the tissues and/or cause toxic effects. The study of biomarkers of exposure to metals, such as metallothioneins, which are responsible for maintaining homeostasis through the regulation of essential metals and detoxification of nonessentials, help in understanding the chemical availability of these contaminants in the environment and their assimilation by biota. In addition, biometric measurements may indicate the effects of metals on the population, such as the weight-to-width ratio and the condition factor, which provide information on the species healthiness. The present study aimed to determine the concentrations of metals and metallothioneins in crabs Ucides cordatus caught in two equatorial mangrove areas with distinct sources of contamination. Two sampling campaigns were carried out in the dry season and two in the rainy season when 104 adult males were collected, cleaned in laboratory and weighed with an analytical balance and measured with a digital caliper. They were then sacrificed to remove hepatopancreas for analysis of metals (Al, Ba, Cd, Cr, Cu, Fe, Mn, Ni, Pb, Sc, Se, Sn, V, and Zn) and metallothioneins. Samples were digested in a digester furnace and analyzed in an atomic emission spectrometer with inductively coupled plasma. Metallothioneins were analyzed by spectrophotometry using a microplate reader. The results showed significant differences in body mass, carapace width and length, and the condition factor between the areas and the collection month. In general, the crabs that presented the highest biometric values were those collected in the mangrove distant from industrialized area. Significant differences were also observed in the levels of metals and metallothioneins between areas and collection month. Metals with the highest concentrations were Fe, Mn, Cu and Zn. There was a strong correlation between the metallothioneins synthesis and the presence of metals. High concentration of metals coincided with higher concentration of metallothioneins. The rainfall led to a higher concentration of metals in the hepatopancreas and consequent synthesis of metallothioneins.